2006
DOI: 10.2981/0909-6396(2006)12[393:pbgeac]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Predation by golden eagle Aquila chrysaetos on semi-domesticated reindeer Rangifer tarandus calves in northeastern Finnish Lapland

Abstract: Calf losses are an acute issue in Fennoscandian reindeer Rangifer t. tarandus management. We studied calf mortality in northeastern Finnish Lapland using 621 calves (304 in 1997 and 317 in 1998) marked with silent mortality transmitters and followed their survival during

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 36 publications
0
45
2
1
Order By: Relevance
“…Round-ups were performed between 20 June and 15 July. The number of calves counted varied between days, but such variation could only marginally influence the calf/female ratio because the critical first few weeks of life occurred before round-ups and mortality during the round-up season is low (< 2%) in this herd (Norberg et al 2006). Because reindeer is monoparous, the number of calves is the same as the number of females with calves.…”
Section: Parametersmentioning
confidence: 89%
“…Round-ups were performed between 20 June and 15 July. The number of calves counted varied between days, but such variation could only marginally influence the calf/female ratio because the critical first few weeks of life occurred before round-ups and mortality during the round-up season is low (< 2%) in this herd (Norberg et al 2006). Because reindeer is monoparous, the number of calves is the same as the number of females with calves.…”
Section: Parametersmentioning
confidence: 89%
“…Natural predators were reported to travel along power line ROW (Foster, 1956in Ball, 2012Paquet et al, 1996;Gurarie et al, 2011). Power lines provide nesting and perching opportunities for golden eagle (Aquila chrysaetos) (Steenhof et al, 1993;Prather and Messmer 2010), which preys on ungulates (Nybakk et al, 2002;Norberg et al, 2006;Johnsen et al, 2007;Hamel and Côté, 2009;Nadjafzadeh et al, 2013).…”
Section: Potential Demographic Impactsmentioning
confidence: 99%
“…Many studies have shown the major role of large terrestrial carnivores on the neonate mortality of large and medium-sized ungulates (see Linnell et al, 1995). Calf mortality is also an important factor in the population dynamics of many reindeer and caribou herds, and predation is suspected as the primary cause of mortality (Miller & Broughton, 1974;Page, 1985;Mahoney et al;, Skogland, 1991Whitten et al, 1992;Adams et al, 1995;Valkenburg et al, 2004;Norberg et al, 2005Norberg et al, , 2006Nieminen, 2010). Caribou herds exposed to predation may lose even 50% of the annual calf crop prior to six months of age (Bergerud, 1980).…”
Section: Introductionmentioning
confidence: 99%